Being There: The Fieldwork Encounter and the Making of Truth - Borneman, John; Hammoudi, Abdellah (University of California Press, 2009)
Challenges to ethnographic authority and to the ethics of representation have led many contemporary anthropologists to abandon fieldwork in favor of strategies of theoretical puppeteering, textual analysis, and surrogate ethnography. In Being There, John Borneman and Abdellah Hammoudi argue that ethnographies based on these strategies elide important insights. To demonstrate the power and knowledge attained through the fieldwork experience, they have gathered essays by anthropologists working in Morocco, Saudi Arabia, Syria, Tanzania, the Canadian Arctic, India, Germany, and Russia that shift attention back to the subtle dynamics of the ethnographic encounter. From an Inuit village to the foothills of Kilimanjaro, each account illustrates how, despite its challenges, fieldwork yields important insights outside the reach of textual analysis.